Optimization of Distribution Routes of Imported Pipeline Products Using Saving Matrix Analysis and System Dynamics - Siregar, Maryadi Tirtana; subekti; Rapi, Amrin (Indonesian Scientific Publication, 2025)
Innovation is carried out systematically to develop and market breakthrough products, systems, or services that can solve customer problems. Companies that do not innovate or are not at a high-quality level become stagnant and can even go bankrupt. PT Arita Prima Indonesia Tbk was established on October 5, 2000, in Jakarta, Indonesia, and engaged in import, distribution, and service for valve, fitting, instrumentation, and control products. The expedition division is responsible for shipping goods to customers. In previous studies, implementing the nearest insert and nearest neighbor methods in shipping route planning can help minimize travel distances and increase the efficiency of the distribution process of imported products. The saving matrix method focuses on adding nearby consumers to complete existing routes. The system dynamics approach shows the unity of interaction between elements of an object within a specific scope that work together to achieve goals. This provides structure to the object, can differentiate it from other objects, and affects the state of the object. The highest total expenditure from month 1 to month 120 was on the carry box car amounting to 2681.32 million rupiah or Rp2,681,320,000. The lowest total expenditure from month 1 to month 120 was on the canter box car amounting to 2503.75 million rupiah or Rp2,503,750. The highest total cost from month 1 to month 120 was on the canter long car with the highest asset value (Rp290,000,000) amounting to 2843.77 million rupiah or Rp2,843,770,000 (two billion eight hundred forty-three million seven hundred seventy thousand rupiah). The lowest total cost from month 1 to month 120 was on the canter box car with the second highest asset value (Rp185,000,000) amounting to 2503.75 million rupiah or Rp2,503,750,000.